Effectiveness of Implementing E-Tickets in the Central Jakarta Police Traffic Police Unit - Indarti, Lintang; Zain, Herlina Muzanah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The increasing pattern of community growth in DKI Jakarta has resulted in the number of vehicles also increasing. So the government has created administrative sanctions in the form of an e-ticket program designed since 2019 to reduce the number of traffic violations. The method used in this research uses a qualitative descriptive approach, where this research was produced through observation, interviews and documentation. To reduce violations, the police are holding outreach to the public with the aim of implementing e-tickets, which can also help the duties of police officers and can make the public have more confidence in the police who are transparent and accountable. So that it is easy for the public to access all information related to violations. The implementation of e-tickets is also useful for taking action against traffic violators fairly. The main target of implementing e-tickets is to discipline the public, as well as to reduce the number of traffic accidents. Apart from that, with this e-ticket implementation program, it is hoped that the public will be more disciplined and orderly in traffic